Identification of (2‐aminopropyl)benzofuran (APB) phenyl ring positional isomers in Internet purchased products. Issue 4 (24th January 2013) - Stanczuk, Andrzej; Morris, Noreen; Gardner, Elizabeth A.; Kavanagh, Pierce
<x xml:space="preserve">Abstract</x> 5‐(2‐Aminopropyl)benzofuran (5‐APB), a 'research chemical' that was first reported by UK authorities to the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA) in 2010, is anecdotally reported to produce a combination of stimulant and entactogenic effects. More recently, in 2011, 6‐(2‐aminopropyl)benzofuran (6‐APB) was identified by Hungarian authorities. To confirm positional isomer identity in Internet purchased products, 4‐ 5‐ 6‐ and 7‐APBs were synthesized and found to be separable by gas chromatography (as heptafluorobutyramide derivatives) and liquid chromatography. The analyses of products purchased from online vendors of 'research chemicals' identified the presence of 5‐ or 6‐APBs. These findings were further confirmed by liquid chromatography‐mass spectrometry and 1H nuclear magnetic resonance spectroscopy. In products containing 6‐APB, the 4‐ positional isomer was also identified and this may have arisen during the manufacturing process. Copyright © 2013 John Wiley & Sons, Ltd.